Anterior cruciate ligament injury/reinjury in alpine ski racing: a narrative review - Jordan MJ; Aagaard P; Herzog W (Dove Medical Press, 2017)
Matthew J Jordan,1 Per Aagaard,2 Walter Herzog1 1Human Performance Laboratory, The University of Calgary, Calgary, AB, Canada; 2Department of Sports Science and Clinical Biomechanics, SDU Muscle Research Cluster (SMRC), University of Southern Denmark, Odense M, Denmark Abstract: The purpose of the present review was to: 1) provide an overview of the current understanding on the epidemiology, etiology, risk factors, and prevention methods for anterior cruciate ligament (ACL) injury in alpine ski racing; and 2) provide an overview of what is known pertaining to ACL reinjury and return to sport after ACL injury in alpine ski racing. Given that most of the scientific studies on ACL injuries in alpine ski racing have been descriptive, and that very few studies contributed higher level scientific evidence, a nonsystematic narrative review was employed. Three scholarly databases were searched for articles on ACL injury or knee injury in alpine ski racing. Studies were classified according to their relevance in relation to epidemiology, etiology, risk factors, and return to sport/reinjury prevention. Alpine ski racers (skiers) were found to be at high risk for knee injuries, and ACL tears were the most frequent diagnosis. Three primary ACL injury mechanism were identified that involved tibial internal rotation and anteriorly directed shear forces from ski equipment and the environment. While trunk muscle strength imbalance and genetics were found to be predictive of ACL injuries in development-level skiers, there was limited scientific data on ACL injury risk factors among elite skiers. Based on expert opinion, research on injury risk factors should focus on equipment design, course settings/speed, and athlete factors (eg, fitness). While skiers seem to make a successful recovery following ACL injury, there may be persistent neuromuscular deficits. Future research efforts should be directed toward prospective studies on ACL injury/reinjury prevention in both male and female skiers and toward the effects of knee injury on long-term health outcomes, such as the early development of osteoarthritis. International collaborations may be necessary to generate sufficient statistical power for ACL injury/reinjury prevention research in alpine ski racing. Keywords: knee injury, return to sport, injury prevention, knee biomechanics, ACL reinjury